PENGARUH BUDAYA ORGANISASI, MOTIVASI, DAN GAJI TERHADAP KINERJA KARYAWAN (Studi kasus PDAM Kabupaten Grobogan) - Pinka Morina; Sri Suryoko; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2013)
The success of a company is usually influenced by the performance of the employee or the work accomplished by an employee in performing duties in accordance with the responsibilities. From the result of performance PDAM Grobogan in recent 5 years, still need to be improved even of the operational aspect there was a decrease. Many factor which could be the cause the decline in performance among others organizational culture, motivation, and salary. The purposes of this study to determine whether there is influence between organizational culture, motivation and salaries to employees performances in Grobogan. This type of research used is explanatory research. The number of samples in this study was 50 respondents drawn by accidental sampling. Multiple regression analysis is Y = 8.551 + 0.193 X1 + 0.344 X2 + 0.066 X3 so it can be seen that the variable organizational culture, motivation and salary is jointly positive effect on variable performance , and which has the greatest influence motivation is variable . Hypothesis test shows that the variable organizational culture, motivation and affect the performance of the employee salary. This is demonstrated by the achievement of all the variable t is greater than t table is 1.677. Organizational culture variables have t 8.682, 7.395 motivation, and variable salary 6,100. As for the F test obtained F count of 28.270. And all of these variables were tested at a significance level of 5 %. Thus the hypothesis is accepted.The advice given to the company is prioritizes honesty in work and reject any form of tip from customer.